Percentage of residual B cells after 2 weeks of rituximab treatment predicts the improvement of systemic sclerosis‐associated interstitial lung disease. Issue 1 (18th October 2021) - Ebata, Satoshi; Yoshizaki, Ayumi; Fukasawa, Takemichi; Yoshizaki‐Ogawa, Asako; Asano, Yoshihide; Kashiwabara, Kosuke; Oba, Koji; Sato, Shinichi
Abstract: The benefit of rituximab (RTX) for systemic sclerosis‐associated interstitial lung disease (SSc‐ILD) has been shown in previous clinical trials. However, predictors of RTX efficacy have not been clarified. We investigated whether B‐cell responsiveness to RTX is related to therapeutic effect. Ten SSc‐ILD patients treated with RTX in an independent clinical trial (Japan Registry of Clinical Trials, jRCTs031180373) were included in this analysis. Peripheral B‐cell counts were examined retrospectively before RTX administration (baseline) and at 2, 4, 12, and 24 weeks after the first RTX administration, along with percent‐predicted forced vital capacity (%FVC) before and 24 weeks after RTX treatment. Relative to baseline, the percentage of residual peripheral blood B cells at 2 weeks after RTX was negatively correlated with the %FVC improvement at the 24‐week assessment ( r = −0.41, p = 0.04). In the subgroup with less than 5% B‐cell persistence at week 2, %FVC at the 24‐week assessment was significantly improved compared to baseline ( p = 0.02). In another subgroup with more than 5% residual B cells, %FVC was not significantly different after 24 weeks compared to baseline ( p = 0.41). In conclusion, the removal rate of B cells after 2 weeks of RTX treatment may be a useful surrogate marker of subsequent SSc‐ILD improvement.